Nanocarbon-based catalysts for selective nitroaromatic hydrogenation: A mini review - Yao, Jiarong; Wang, Li; Xie, Dong; Jiang, Linxuan; Li, Jiantong; Fang, Xiaomin (Frontiers in Chemistry, 2022)
Selective hydrogenation of nitroaromatics to the corresponding anilines is a key topic for research in fine chemical industrial fields. Nanocarbon materials with good chemical stability, high electrical conductivity, and good mechanical performance have been regarded as promising candidates in the catalytic field, and have shown a wide range of applications in recent years. Controllable synthesis on the structure, morphology, and active sites of nanocarbon-based catalysts is vital to the development of highly efficient catalysts. In this mini-review, we summarize the recent progresses of nanocarbon materials by focusing on the synthesis approaches and their corresponding nanostructures, including carbon nanofibers, carbon nanotubes, graphene, porous carbon, carbon spheres, and metal organic framework-derived carbon materials. The design and catalytic performance of these nanocarbon materials have been systematically discussed. Finally, the emerging challenges and future prospective for developing advanced nanocarbon-based catalysts are outlined.